2003
DOI: 10.1007/s10142-003-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the genomic region linked with apomixis in Pennisetum/Cenchrus

Abstract: Apomixis is defined as asexual reproduction through seeds, although this outcome can be achieved by multiple pathways. Since little is known about the molecular control of these pathways, how they might intersect is also a mystery. Two of these pathways in the grass family, diplospory and apospory, are receiving attention from molecular biologists. Apospory in Pennisetum/Cenchrus, two genera of panicoid grasses, results in the formation of four-nucleate embryo sacs that lack antipodals. Sexual reproduction fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 57 publications
5
45
0
1
Order By: Relevance
“…Since P. squamulatum is considered as a potential donor for desirable traits for pearl millet improvement, the prospects of utilization of hybrids is high, not only with respect to introgression of desirable traits, but also to understand complex traits such as perenniality and apomixis. Genetic analysis involving P. squamulatum (2nϭ54) cytotypes revealed apomixis (apospory) under control of a complex locus designated as ASGR (Apospory Specific Genomic Region), localized on a single squamulatum chromosome, and characterized by hemizygosity and suppressed recombination (Ozias-Akins et al 2003, Akiyama et al 2006. Similar analyses involving 2nϭ56 cytotype shall be important to identify the presence of same or different phenomenon as in 2nϭ54 cytotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since P. squamulatum is considered as a potential donor for desirable traits for pearl millet improvement, the prospects of utilization of hybrids is high, not only with respect to introgression of desirable traits, but also to understand complex traits such as perenniality and apomixis. Genetic analysis involving P. squamulatum (2nϭ54) cytotypes revealed apomixis (apospory) under control of a complex locus designated as ASGR (Apospory Specific Genomic Region), localized on a single squamulatum chromosome, and characterized by hemizygosity and suppressed recombination (Ozias-Akins et al 2003, Akiyama et al 2006. Similar analyses involving 2nϭ56 cytotype shall be important to identify the presence of same or different phenomenon as in 2nϭ54 cytotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Goel et al (2003) reported for the first time the FISH-aided localization of the apomixis locus on metaphase chromosomes and they claimed that its vicinity to the centromere in Cenchrus ciliaris and to centromeric repeats in P. squamulatum could cause the repression of recombination at the same locus in these species. Further FISH analyses on pachytene chromosome preparations of the same species are in favour of these assumptions (Akiyama et al 2004;Akiyama et al 2005;Ozias-Akins et al 2003). FISH using pachytene chromosomes as targets offers superior spatial resolution of adjacent probes compared to metaphase chromosomes and display clearly the dense heterochromatic regions on the chromosomes and so allow the assignment of a probe position in relation to the structural organization of its surrounding chromosome context (de Jong 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This asexual reproduction provides the advantage of rapid multiplication allowing the development of a significant aboveground yield and consequently the formation of an extremely dense ground cover by C. ciliaris (Ozias-Akins et al 2003;Akiyama et al 2005;Miles 2007;Ozias-Akins and Van Dik 2007;Singh et al 2007). Asexual reproduction may have benefits in stable environments, while sexual reproduction offers a net advantage by allowing more rapid generation of genetic diversity allowing adaptation to a changing environment.…”
Section: Facultative Nature Of Apomixis In Cenchrus Ciliarismentioning
confidence: 99%
“…Cytogenetic investigations of tetraploid C. ciliaris have demonstrated that the ASGR is located near the centromere in a genomic region that is hemizygous and heterochromatic (condensed part of chromatin genetically inactive) (Goel et al 2003(Goel et al , 2006Ozias-Akins et al 2003;Akiyama et al 2005). The ASGR-carrier chromosome has a unique morphological characteristic when compared with other chromosomes in the genome (Akiyama et al 2005) and is~20 Mb larger than its presumed homologous chromosomes (Goel et al 2003;Akiyama et al 2005).…”
Section: Facultative Nature Of Apomixis In Cenchrus Ciliarismentioning
confidence: 99%
See 1 more Smart Citation